Review of Susan Thomas. 2009. Cuban Zarzuela: Performing Race and Gender on Havana’s Lyric Stage. Urbana and Chicago: University of Illinois - Newland, Marti (Current Musicology, 2010)
In Cuban Zarzuela: Performing Race and Gender on Havana’s Lyric Stage, musicologist Susan Thomas draws on her years of archival work in Cuba and the work of a broad collection of scholars including Homi Bhabha, Judith Butler, Karen Henson, and Robin Moore to detail the development and performance practices of an understudied genre of Cuban opera, “zarzuela.” Emerging as a well-received genre in Havana theaters during the early twentieth century, Cuban zarzuela incorporates Spanish light opera and Afrocuban musical characteristics into one-act operettas featuring a number of racial and nationalist archetypes endemic in turn-of-the-century Cuba: the “mulatta” woman, the “black” man, the “white” woman, and the “white” man. Thomas organizes the text into studies of each of these subject positions to reveal how Cuban zarzuela served as a platform to establish a distinctly Cuban opera genre, as well as to provide a respectable social outlet for Cuba’s white, female bourgeoisie. A rich example of the confluence of nationalism, race, gender, class, art and popular music, this genre allows the author to analyze a vast swath of key polemics challenging the modern West.